Lesson Study as a Strategy to Improve Mathematics Learning Based on the Learning Styles and Levels of Understanding of Middle School Students - Rofiki, Imam; Darmawan, Puguh; Slamet, Slamet; Wahyuni, Sri; Alaiya, Syekha Vivi; Sani, Mutiara (Universitas Islam Sultan Agung, 2025)
Mathematics learning must consider students’ diverse needs to achieve optimal outcomes, including differences in learning styles, levels of understanding, and learning difficulties. Applying Bloom’s Taxonomy helps teachers design more effective strategies, yet many still neglect thorough planning, treating it as a yearly routine. To overcome this, teacher collaboration is essential. This study aimed to facilitate a lesson study involving mathematics teachers from the Mathematics Teachers’ Association (MGMPS) in Banyuwangi, junior high school students, pre-service teachers, and mathematics education lecturers. Using a descriptive qualitative approach, the research was conducted at a junior high school in Banyuwangi. The research used qualitative analysis with observations, reflections, and triangulation to align teaching strategies with students’ learning styles and understanding levels. The findings show that lesson study effectively enhances mathematics learning by accommodating students’ learning diversity. Through the stages of planning, observation, and reflection, teachers developed more responsive and differentiated lessons. Moreover, lesson study promoted professional growth among teachers through collaboration and reflective practice. Overall, lesson study provides a sustainable and adaptive approach to fostering inclusive and high-quality mathematics learning. Keywords: Lesson study, learning style, mathematics learning